Connotative Meanings in “Red (Taylor’s Version)” Album by Taylor Swift - Syaharani, Imelda Putri; Zuraida, Ida (JALL (Journal of Applied Linguistics and Literacy), 2025)
Connotative meaning refers to the emotional and associative implications from words literal definition, and song lyrics are often used by the creator as an intermediary to convey the contents of thoughts and feelings with various types of language styles. This study aims to identify types of connotative meanings and to examines how the connotative meanings in the song lyrics contribute to the overall emotional impact or message of the song in Red (Taylor’s Version) album by Taylor Swift. The study applies a qualitative descriptive method. The theoretical foundation is based on Leech’s (1981) theory of semantics, with a focus on identifying and analyzing three types of connotative: positive, negative, and neutral based on Michael Halley’s (1980) theory on connotative functions. The analysis follows several stages: lyrics selection, identification of connotative expression, classification by type, and interpretation within the context of the album’s themes. The analysis findings indicate that the three types of connotative meanings are consistently used throughout the album, while precise number for each connotative category in Red (Taylor’s Version) are not definitively established, the album predominantly features negative emotional tones, consistent with its themes of love and loss. By deeper meaning and clearer translation, this study aims to avoid cultural misunderstanding or miscommunication through figurative language.